Technologies and their resources in higher cello education: The digital benefits in face-to-face higher cello teaching - Reirís Rodríguez, Alba (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
As a result of the COVID-19 pandemic, music teaching in higher music conservatories is in a state of obligatory openness to the use of technologies and audiovisual media in its methodology. The aim of this research is to study in depth the theoretical and practical use of technologies and audiovisual media in the instrumental teaching of the cello. The aim is to prove that the use of technologies and all that they encompass can significantly improve the teaching of the instrument.